19th AIAA/CEAS Aeroacoustics Conference 2013
DOI: 10.2514/6.2013-2296
|View full text |Cite
|
Sign up to set email alerts
|

An Investigation of the Inlet and Exhaust Noise Sources of Turbofan Using Linear Microphone Array

Abstract: This paper presents noise source location results for a turbofan engine with the bypass ratio of 2.4 obtained from engine static test, in which the engine was installed on aircraft. Source location data from this test was used to develop engine inlet sound absorbing liner and to design the aircraft fuselage sound insulation device. A linear array of 32 microphones was used in this program to determine the jet noise source distribution for the exhaust and the fan noise from inlet. Aeroacoustic beamforming with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…However, the literature is very limited in this regard. In particular case studies, [6][7][8] although the duration of averaging (recording) is reported, 18 these cases are restricted to the use of conventional algorithms capable for detecting standing sources. No direct recommendations were found in the literature for the appropriateness of averaging of PAM records in application of the ROSI algorithm.…”
Section: Notes On Averaging Of Pam Recordsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the literature is very limited in this regard. In particular case studies, [6][7][8] although the duration of averaging (recording) is reported, 18 these cases are restricted to the use of conventional algorithms capable for detecting standing sources. No direct recommendations were found in the literature for the appropriateness of averaging of PAM records in application of the ROSI algorithm.…”
Section: Notes On Averaging Of Pam Recordsmentioning
confidence: 99%
“…The subjects of experimentation are mostly not industrial ventilating fans but aero-engine fans. 3,4,[6][7][8] The ROSI algorithm is still rarely applied. 1,4 In the cases when multiple microphones are used in diagnostics of industrial ventilating fans, the supplement of acoustics measurements by aerodynamic experiments is either lacking 5 or is usually confined to global data.…”
Section: Introductionmentioning
confidence: 99%